A Universal and Facile Way for the Development of Superior Bifunctional Electrocatalysts for Oxygen Reduction and Evolution Reactions Utilizing the Synergistic Effect. Issue 47 (29th September 2014) - Zhu, Yinlong; Su, Chao; Xu, Xiaomin; Zhou, Wei; Ran, Ran; Shao, Zongping
Abstract Increasing energy demands have stimulated intense research activities on reversible electrochemical conversion and storage systems with high efficiency, low cost, and environmental benignity. It is highly challenging but desirable to develop efficient bifunctional catalysts for both the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER). A universal and facile method for the development of bifunctional electrocatalysts with outstanding electrocatalytic activity for both the ORR and OER in alkaline medium is reported. A mixture of Pt/C catalyst with superior ORR activity and a perovskite oxide based catalyst with outstanding OER activity was employed in appropriate ratios, and prepared by simple ultrasonic mixing. Nanosized platinum particles with a wide range of platinum to oxide mass ratios was realized easily in this way. The as‐formed Pt/C–oxide composites showed better ORR activity than a single Pt/C catalyst and better OER activity than a single oxide to bring about much improved bifunctionality (ΔE is only ≈0.8 V for Pt/C–BSCF; BSCF=Ba0.5Sr0.5Co0.8Fe0.2O3−δ), due to the synergistic effect. The electronic transfer mechanism and the rate‐determining step and spillover mechanism were two possible origins of such a synergistic effect. Additionally, the phenomenon was found to be universal, although the best performance could be reached at different platinum to oxide mass ratios for different oxide catalysts. This work thus provides an innovative strategy for the development of new bifunctional electrocatalysts with wide application potentials in high‐energy and efficient electrochemical energy storage and conversion.